Motivations for Mobilization: Comparing Urban and Suburban Residents' Participation in the Politics of Planning and Development. Issue 4 (July 2022) - Moore, Aaron A.
This paper compares and contrasts suburban and urban residents' attitudes and behavior toward development by comparing the frequency and motivation for mobilization of residents in the suburbs of Surrey, British Columbia, and Brampton, Ontario, with residents of their respective metropolitan urban cores. It finds that suburban residents engage less in planning politics than their urban counterparts and that they are more likely to oppose development than urban residents. However, while some variation exists in the concerns suburban and urban residents raise when they express their opposition to development, overall, the concerns of residents in suburbs and urban cores are largely the same. The data suggest that what differences exist between suburban and urban residents in the politics of urban development and planning likely arise due to the varying nature and prevalence of development encroaching on existing neighborhoods, rather than from underlying cultural differences.